In the heat of the moment, secrets will out: Oil price uncertainty and firm green innovation disclosure - Huang K; Chi J; Liao J; Yuen MK (Elsevier Inc, 2025)
This study investigates the relationship between oil price uncertainty and corporate green innovation disclosure behaviour. Drawing on a textual analysis of annual reports and social responsibility reports of Chinese listed companies, we construct a measure for the intensity of corporate green innovation disclosure. We find a significantly positive relationship between oil price volatility and the level of green innovation disclosure. This relationship remains robust after conducting robustness tests and addressing potential endogeneity. Further analysis reveals that this positive association is moderated by several firm-level factors, including environmental performance, legitimacy demands, and political connections. Additionally, the positive relationship is more pronounced in firms subject to higher regional environmental regulation intensity and market-based green initiatives. Our findings contribute new evidence to corporate sustainable development, demonstrating that energy uncertainty significantly influences information transparency in green innovation disclosure.